Odontogenic keratocysts tumor with iliac crest graft - Vilcapoma Guerra, Henry Jesús (2011)
The odontogenic keratocysts tumor is a benign intraosseous uni- or multicystic tumor, characterized by the presence of stratified squamous parakeratinized epithelium, with a aggressive potential and infiltrative behavior. Its importance lies in its high rate of recurrence. We report a case of a male patient of 46 years, asymptomatic, with a volume augmentation of the right side of the face. After the clinical, histopathological and radiographic examination, it was diagnosed as Odontogenic Keratocysts Tumor. Surgical treatment was performed with satisfactory results.